2002
DOI: 10.4296/cwrj2701025
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Kinetics of Geometric Isomers of Model Naphthenic Acids in Athabasca River Water

Abstract: The rates ofbiodegradation of six model naphthenic acids (NA$ byheterotrophic bacteria were compared. Specifically, the biodegradation of cis-and trans-geometric isomers of 4-methylcyclohexaneacetic acids (4MACH), 4- hours-1, while the values of K for the corresponding rzi-isomers were 0.7 " 10-3 and 0.6 t 10-'hours-r, respectively. For all the model NAs investigated, the trans tsomers degraded more rapidly than the respective czl isomers. The range of K measured at 10oC and 30"C of the trans-isomers were betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 6 publications
2
17
1
Order By: Relevance
“…For non-branched carboxylic acids, the addition of methyl groups hindered b-oxidation (Herman et al, 1993;Alexander, 1999;Smith et al, 2008) and only mixed bacterial populations degraded recalcitrant NAs with methyl substitutions on the cycloalkane rings (Herman et al, 1993;Headley et al, 2002a, b). Differences in NA degradation rates for different geometric isomers have also been observed, whereby intramolecular hydrogen bonding occurring with the cis-isomers makes them less bioavailable and difficult to metabolize (Headley et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…For non-branched carboxylic acids, the addition of methyl groups hindered b-oxidation (Herman et al, 1993;Alexander, 1999;Smith et al, 2008) and only mixed bacterial populations degraded recalcitrant NAs with methyl substitutions on the cycloalkane rings (Herman et al, 1993;Headley et al, 2002a, b). Differences in NA degradation rates for different geometric isomers have also been observed, whereby intramolecular hydrogen bonding occurring with the cis-isomers makes them less bioavailable and difficult to metabolize (Headley et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of Cys used [10 −2 -10 −1 mol dm −3 ] were chosen to be 1-2 orders of magnitude larger than that of the MC [10 −4 -10 −2 mol dm −3 ]. The ionic strength of the solutions was kept constant at 0.20 mol dm −3 using NaClO 4 . The temperature of the solution and its pH were both maintained at 25±0.1 • C and 7.0 ± 0.1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Toma et al [3] reviewed linkage isomerization reactions from the aspect of kinetics and mechanisms involved, some focusing on selected cases of direct formation, as well as on electrochemical, photochemical, thermal and pH-induced generation of linkage isomers. The biodegradation kinetics of geometric isomers of model naphthenic acid in water has been studied by Peru et al [4]. The rates of biodegradation of six model naphthanic acids by heterotrophic bacteria were compared.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that the molecular weight (Scott et al, 2005;Biryukova et al, 2007;Whitby, 2010) and chemical structure (Headley et al, 2002;Smith et al, 2008;Han et al, 2008) of NAs can influence their biodegradation. For instance, determinants of recalcitrant NAs can include the following: (i) a higher degree of alkyl-substituted aliphatic chains (Smith et al, 2008;Han et al, 2008), (ii) tertiary substitution at positions other than the b-position to the carboxylic acid of the main carbon chain, (iii) methyl substitution on the cycloalkane rings (Herman et al, 1993;Smith et al, 2008), (iv) increased cyclicity (Han et al, 2008), (v) evenness of the carbon side chain, and (vi) cis-isomerism in alicyclic acids (Headley et al, 2002;Holowenko et al, 2002). Ozonation could change the molecular weight and chemical structure of NAs by decomposing long chains and by breaking highly-branched and cyclic carboxylic fractions, thereby improving their biodegradation.…”
Section: Removal Of Nasmentioning
confidence: 99%